THU0450 Diagnostic relevance of organ biopsies in anca associated vasculitis. (12th June 2018) - Kronfeldner, J.; Eifert, J.; Quickert, S.; Oelzner, P.; Busch, M.; Kroegel, C.; Wolf, G.; Neumann, T.
Abstract : Background: The diagnostic workup of ANCA-associated vasculitis (AAV) is a challenge due to the possible multi-organ involvement and the wide range of differential diagnosis. Before classification, vasculitis needs to be proofed by clinical or histopathologic signs. Objectives: We aimed to evaluate specific histopathologic features of organ biopsies and their contribution to the diagnosis of vasculitis and to the classification of specific AAV subgroups. Methods: Retrospective, single-centre cohort study in patients with granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA), classified by ACR-criteria, who have received at least one organ biopsy. Characteristic histopathologic features were analysed and compared between AAV subgroups, organ systems and ANCA-status (Chi-square-test). Results: 306 patients (GPA n=154, MPA n=58, EGPA n=94) diagnosed between 1990–2017 were included. All biopsies were taken at active stage of GPA, MPA or EGPA at initial diagnosis (n=415) or during flair of the disease (n=36). 168 patients had a renal biopsy, 185 patients had 283 non-renal biopsies (1 biopsy in 102 pts, 2 different organ biopsies in 68 pts, >2 in 15 pts). In kidney biopsies glomerulonephritis was described in 78.6%, unspecific inflammation in 26.8% and normal tissue in 1.2%. In non-renal biopsies vasculitis, granuloma, tissue eosinophilia, unspecific inflammation or normal tissue were reported in patients with GPA 32.9/29.4/21.2/71.8/9.4%, MPA 27.3/9.1/27.3/90.9/9.1% and EGPA 20.2/10.1/67.4/73.0/20.2%; p<0.0001 (lung n=103, 13.6/13.6/37.9/71.8/3.9%; skin n=35, 42.8/11.4/40.0/51.4/1.4%; upper respiratory tract n=98, 19.3/16.3/37.7/72.4/8.2%; peripheral nerves n=7, 14.3/14.3/0/14.3/42.8%; p<0.0001). According to the ANCA status the distribution was 31.1/25.2/28.3/68.9/10.7% in ANCA+patients and 20.8/11.1/62.5/79.2/19.4% in ANCA- patients (p<0.0001). Diagnosis of vasculitis was based on biopsy result in 2% of GPA, none of MPA and 8% of EGPA patients, but ACR criteria were only fulfilled including a characteristic biopsy in 6.6% of GPA and 35.5% of EGPA patients. Assignment to GPA, MPA and EGPA by application of the EMA algorithm were only possible in consideration of a characteristic non-renal biopsy in 2.8/0/21.9% and of a characteristic non-renal and/or renal biopsy in 4.7/14.6/28.1% of all patients. Conclusions: Histologic proof of vasculitis remains the gold standard of AAV diagnostic, however the diagnostic value is most prominent for renal biopsies. Distribution of various histopathologic features is different among AAV subgroups (GPA, MPA, EGPA) and varies between different organ biopsies. While classification of GPA and MPA is only in a few cases based on histopathology, in EGPA a characteristic histopathology is necessary for classification in almost one third of patients. Disclosure of Interest: None declared